ANALISIS DAYA OUTPUT DAN EFISIENSI KINCIR AIR SUDU MIRING YANG BEKERJA PADA SALURAN HORIZONTAL - Rahmat Boli; Abdul Makhsud; Mahmuddin Tahir (Gorontalo Journal of Infrastructure and Science Engineering, 2018)
Abstract : Water wheels angle blade shape with a diameter of 1,000 m wheels, blade length of 0.25 m, and a blade width of 0.3 m. This study aims to determine the power and efficiency of the waterwheel. To test the water mill, then made a model of open channel with a channel length of 12.25 m, a width of 0.334 m channel, channel height of 6.0 m, and the angle of 450. The waterwheel power and efficiency can be determined by varying the flow rate of 0.050 m3/s to 0,032 m3/s at a load of 2 kg to 8 kg. Measurement of the flow rate by method of filling the bucket with a bucket voleme 50 L. To determine the flow rate through the duct bucket volume divided by the time it takes to fill the bucket.Abstrak : Kincir air bentuk sudu miring dengan diameter roda 1,000 m,  panjang sudu 0,25 m, dan lebar sudu 0,3 m. penelitian ini bertujuan untuk mengetahui daya dan efisiensi kincir air. Untuk menguji kincir air tersebut, maka dibuatkan model saluran terbuka dengan panjang saluran 12,25 m, lebar saluran 0,334 m, tinggi saluran 6,0 m, dan sudut kemiringan 450. Daya dan efisiensi kincir air dapat diketahui dengan memvariasikan debit aliran 0,050 m3/s sampai 0,032 m3/s pada beban 2 kg sampai 8 kg. Pengukuran debit aliran dengan metode mengisi ember dengan voleme ember 50 L. Untuk mengetahui debit aliran yang melalui saluran maka volume ember dibagi dengan waktu yang dibutuhkan untuk mengisi ember tersebut.